Evaluation of the Genotoxic and Antigenotoxic Potential of the Alkaloid Punarnavine from Boerhaavia diffusa - Aher, Vaibhav; Chattopadhyay, Pronobesh; Goyary, Danswrang; Veer, Vijay (Planta Medica, 2013)
Boerhaavia diffusa is a traditional herbal medicine extensively used in the Ayurveda and Unani forms of medicine in India and many parts of the world. Different parts of the plant are used as an appetizer, alexiteric, eye tonic, for flushing out the renal system, and to treat blood pressure. This study was conducted to evaluate the in vivo genotoxic and/or antigenotoxic potential of punarnavine, a separated alkaloid from the root of B. diffusa using toxicity studies (OECD guideline 474, 1997). The genotoxic and antigenotoxic potential of punarnavine was assayed using the comet assay on lymphocytes, liver, spleen, brain, and bone marrow as well as using the micronucleus test in bone marrow cells including the in vitro chromosomal aberration test. The results demonstrated that none of the tested doses of punarnavine showed genotoxic effects by the comet assay, or clastogenic effects in the micronucleus test. On the other hand, for all cells evaluated, the three tested doses of punarnavine promoted inhibition of DNA damage induced by cyclophosphamide. Based on these results, we concluded that punarnavine, an alkaloid from the Boerhaavia diffusa root, has no genotoxic or clastogenic effects in our experimental conditions. However, it caused a significant decrease in DNA damage induced by cyclophosphamide. It is suggested that the antigenotoxic properties of this alkaloid may be of great pharmacological importance and beneficial for cancer prevention.
Keywords: punarnavine; antigenotoxic effects; comet assay; micronucleus test; chromosome aberration test; Boerhaavia diffusa; Nyctaginaceae